High Rate of Protein Coding Sequence Evolution and Species Diversification in the Lycaenids - Pellissier, Loïc; Kostikova, Anna; Litsios, Glenn; Salamin, Nicolas; Alvarez, Nadir (Frontiers in Ecology and Evolution, 2017)
Understanding the variations in the rate of molecular evolution among lineages may provide clues on the processes that molded extant biodiversity. Here, we report the high rate of molecular evolution in Lycaenidae and Riodinidae compared to other families of butterflies (Papilionoidea). We assembled a phylogeny of butterflies using eight molecular markers and comprising 4891 species. We found that the rate of molecular evolution is higher in Lycaenidae and Riodinidae compared to the other families, but only the nuclear gene Wingless showed a marked difference, while Elongation factor 1-alpha showed a more moderate difference. In contrast, the gene Cytochrome Oxidase subunit 1 showed no difference between lycaenids as well as riodinids, and other butterflies. In parallel, we calculated the rates of diversification in all subfamilies of the Papilionoidea using the method-of-moments estimator for stem-group ages, which does not require a fully solved phylogeny for the target clades. We found that the Nemeobiinae and Lycaeninae, from the Riodinidae and Lycaenidae families, respectively, had the highest rate of diversification among all subfamilies. Among the life-history traits that could explain differences in molecular evolution and diversification rate, lycaenids display mutualistic or antagonistic interactions with ants, a higher level of host plant specialization and reduced dispersal abilities compared to other butterfly families. Since the current study is limited by the unique event of apparition of myrmecophily analyzed, the relationship with traits cannot be evaluated statistically. Future studies should measure myrmecophily and dispersal abilities quantitatively across a more detailed phylogeny of lycaenids to test for an association between shifts in the strength of mutualism, rates of molecular evolution and the diversification of lineages.